Expression analysis of microRNA and lncRNA in visceral adipose tissue of obese and non-obese individuals - A. Bairqdar; D. E. Ivanoshchuk; O. V. Tuzovskaya; N. S. Shirokova; E. Kashtanova; Y. V. Polonskaya; Y. I. Ragino; E. V. Shakhtshneider (Вавиловский журнал генетики и селекции, 2025)
Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) play important roles in all biological processes,  including adipogenesis, lipid metabolism, and insulin response. Analyzing expression patterns of lncRNAs and miRNAs  in human visceral fat tissue can enhance our understanding of their roles in metabolic disorders. Our research aims to investigate the expression of lncRNAs (ASMER1, SNHG9, P5549, P19461, and GAS5) and miRNAs (miR-26A, miR-222, miR-221, and miR-155) in visceral adipose tissues of individuals with abdominal obesity (n = 70) compared to their le vels in non-obese participants (n = 31), using Real-Time PCR. Among the tested miRNAs, only miR-26A was significantly downregulated in the visceral adipose tissue of obese individuals, with no significant change in the expression of miR- 26A in obese people with or without type 2 diabetes. Similarly, of the tested lncRNAs, only GAS5 showed significantly higher expression levels in obese patients with type 2 diabetes (T2D) (n = 10) compared to obese patients without T2D (n = 60). To test possible interactions between the analyzed non-coding RNAs, we used Spearman’s bivariate correlation test. GAS5 expression levels showed a weak negative correlation (p < 0.05, rs = 0.25) with miR-155 levels in obese patients only. Conversely, a strong positive correlation (p < 0.01, rs = 0.92) between SNHG9 and GAS5 was found in the non-obese group, with a weaker correlation in abdominally obese patients (p < 0.01, rs = 0.67); additionally, miR-26A and miR-155 levels were moderately correlated in the non-obese group (p < 0.05, rs = 0.47) and were found to correlate weakly in obese patients (p < 0.05, rs = 0.26). Our results showed that abdominally obese participants de monstrated higher expression levels of miR-26A in visceral adipose tissue and a significantly lower correlation  between GAS5 and SNHG9 expression when compared to non-obese subjects.